Aqueous dispersion of cerium (III) carbonate particles
By using aqueous dispersions of cerium (III) carbonate particles with specific particle size ranges and capped ligands, the problem of loss of tone retention under light is solved, and better color and gloss retention is achieved .
Patent Information
- Application Number
- CN202180029442.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2020-03-20
- Filing Date
- 2021-02-09
- Publication Date
- 2025-02-07
- Estimated Expiration
- 2041-02-09
AI Technical Summary
Existing external paint coatings are prone to tone retention loss under light, resulting in fading and undesirable color formation, and UV absorbers and antioxidants are in limited effect in most cases.
An aqueous dispersion of cerium (III) carbonate particles having a z-average particle size in the range of 5 nm to 500 nm, and an amine carboxylic acid or a salt thereof, a phosphonic acid or a salt thereof or a polymerization functionalized with a carboxylic acid group is added therein. The substance acts as a capping ligand to stabilize the particles and prevent agglomeration.
The fading of the coating and undesired color formation are significantly reduced, improving the retention of color and gloss, especially under UV light.
Abstract
Description
[0001] Citations of Related Applications
[0002] This application claims priority to U.S. Provisional Application No. 62 / 992,411, filed on March 20, 2020. Background Art
[0003] In the field of exterior paints, it is desirable to have a painted substrate that maintains a bright appearance over an extended period of time. This "freshly painted" appearance can be measured by three interrelated properties: stain resistance (DPUR), gloss retention, and hue retention. Of these, hue retention is of particular concern as darker and deeper colors become more popular in exterior applications.
[0004] The loss of hue retention is also called fading, which is believed to be caused by TiO 2 The photocatalytic degradation of polymers and colorants was induced by TiO 2 Used as an opaque pigment in most paint formulations. TiO 2 The particles absorb UV light and in the presence of water generate highly reactive hydroxyl groups which reactively degrade the polymer backbone and colorant causing gloss loss, fading and undesirable color formation.
[0005] Attempts to mitigate degradation of exterior coatings have been largely accomplished by using UV absorbers to block UV light to prevent free radical formation and antioxidants to quench free radicals before polymer or colorant degradation occurs. Unfortunately, UV absorbers require a sufficiently long path length for absorption to occur and are therefore only useful in transparent (i.e., TiO-free) 2 ) top coating. Antioxidants such as hindered amines, hindered phenols, carbon-centered groups, phosphites, and sulfides form undesirable films and therefore only provide short-term effective protection. Therefore, it would be advantageous in the field of exterior coatings to find more effective ways to achieve color retention and reduce undesirable color formation in coated surfaces. Summary of the invention
[0006] The present invention solves the need in the art by providing a composition comprising an aqueous dispersion of cerium (III) carbonate particles having a z-average particle size in the range of 5 nm to 500 nm, the composition further comprising a capping ligand which is an amine carboxylic acid or a salt thereof, an amine phosphonic acid or a salt thereof, or a polymer functionalized with a carboxylic acid group or a salt thereof. DETAILED DESCRIPTION
[0007] In a first aspect, the present invention is a composition comprising an aqueous dispersion of cerium (III) carbonate particles having a z-average particle size in the range of 5 nm to 500 nm. The dispersion preferably also comprises an end-capping ligand, which is an amine carboxylic acid or salt thereof, an amine phosphonic acid or salt thereof, or a polymer functionalized with a carboxylic acid group or salt thereof. It is believed that the end-capping ligand stabilizes the particles to prevent agglomeration.
[0008] In another aspect, the present invention is a method for preparing an aqueous dispersion of nanoscale cerium (III) carbonate particles, the method comprising the steps of mixing in water a) a water-soluble cerium (III) ammonium salt, b) a water-soluble carbonate and c) a capping ligand, wherein the capping ligand is an amine carboxylic acid or a salt thereof, an amine phosphonic acid or a salt thereof, or a polymer functionalized with a carboxylic acid group or a salt thereof; wherein the relative proportions of a), b) and c) are such that the z-average particle size of the resulting cerium (III) carbonate particles is in the range of 5 nm to 500 nm.
[0009] As used herein, "nanoscale cerium (III) carbonate particles" refers to cerium (III) carbonate particles having a z-average particle size of no more than 500 nm as measured by dynamic light scattering. The term "nanodispersion" refers to an aqueous dispersion of nanoscale cerium (III) carbonate particles. In another aspect, the nanoscale cerium (III) carbonate particles have a z-average particle size of no more than 300 nm; in another aspect, no more than 200 nm; and in another aspect, no less than 50 nm.
[0010] As used herein, "water-soluble cerium (III) ammonium salt" refers to a cerium (III) ammonium salt that is at least 10% soluble in water in the proportion used. A preferred water-soluble cerium (III) ammonium salt is cerium (III) ammonium nitrate. Similarly, the term "water-soluble carbonate" refers to an alkali metal or ammonium carbonate or bicarbonate that is at least 10% soluble in water in the proportion used. Examples of water-soluble carbonates include sodium carbonate, potassium carbonate, ammonium carbonate, sodium bicarbonate and potassium bicarbonate, with ammonium carbonate being preferred.
[0011] As used herein, "amine carboxylic acid" is a compound comprising at least one amine group and at least one carboxylic acid group. Preferably, the amine carboxylic acid is aminoacetic acid or a salt thereof; preferably, the aminoacetic acid comprises at least two carboxylic acid groups; more preferably, the aminoacetic acid is diacetamide, triacetamide or tetraacetamide, examples of which include ethylenediaminetetraacetic acid (EDTA), ethylenediaminediacetic acid (EDDA) and nitrilotriacetic acid (nitrotriacetic acid, aminotriacetic acid, nitrolotriacetic acid, NTA).
[0012] For example, the polymer functionalized with carboxylic acid groups can be a homopolymer resulting from the homopolymerization of carboxylic acid-containing monomers (such as acrylic acid), or a copolymer resulting from the copolymerization of carboxylic acid-containing monomers with one or more additional monomers (which do not require carboxylic acid functionalization). An example of a homopolymer functionalized with carboxylic acid groups is polyacrylic acid (PAA).
[0013] "Amine phosphonic acid" refers to a compound comprising at least one amine group and at least one phosphonic acid group. The end-capping ligand may include one or more phosphonic acids and one or more carboxylic acid groups and salts thereof. Examples of amine phosphonic acids include aminotrimethylphosphonic acid (ATMP), 6-amino-2-[bis(carboxymethyl)amino]hexanoic acid, and N-(phosphonomethyl)iminodiacetic acid (PIDA).
[0014] A water-soluble cerium (III) ammonium salt (preferably ammonium cerium (III) nitrate), a water-soluble carbonate (preferably ammonium carbonate) and a capping ligand are advantageously mixed together in water at a pH in the range of 8 (preferably 9) to 12 (preferably 11) under conditions sufficient to produce a nano-dispersion of cerium (III) carbonate particles. The mole: mole ratio of the water-soluble cerium (III) ammonium salt to the water-soluble carbonate is preferably in the range of 2: 1 (more preferably 1: 1) to preferably 1: 20 (more preferably to 1: 10); the mole: mole ratio of the water-soluble cerium (III) ammonium salt to the capping ligand is preferably in the range of 50: 1 (more preferably 30: 1) to 1: 1. The reaction is typically carried out at or near ambient temperature and the reaction is typically complete within one hour.
[0015] In another aspect, the present invention is a method for preparing an aqueous dispersion of nanoscale cerium (III) carbonate particles, the method comprising the steps of mixing in water a) a water-soluble cerium (III) ammonium salt, b) a water-soluble carbonate and c) a capping ligand, wherein the capping ligand is an amine carboxylic acid or a salt thereof, an amine phosphonic acid or a salt thereof, or a polymer functionalized with a carboxylic acid group or a salt thereof; wherein the relative proportions of a), b) and c) are such that the z-average particle size of the resulting cerium (III) carbonate particles is in the range of 5 nm to 500 nm.
[0016] Based on the weight of water and cerium (III) carbonate, the concentration of cerium (III) carbonate in water is preferably in the range of 0.2 wt %, more preferably 0.5 wt % and most preferably 1 wt % to 25 wt %, more preferably 21 wt %. More typically, the concentration of the reactants is adjusted to form a final dispersion of 1 to 5 wt % solids; compositions with higher solids content can be prepared by centrifugation, followed by removal of the supernatant or vacuum removal of water.
[0017] In another aspect, the present invention is a composition comprising a polymer and cerium carbonate (III) particles. In this respect, the polymer preferably forms a solution or dispersion with a liquid. In one embodiment of this aspect of the invention, the composition is an aqueous dispersion of polymer particles (latex) and cerium carbonate (III) particles. In this respect, the particle size of the dispersed cerium carbonate (III) particles is not limited. Larger cerium carbonate (III) particles, especially particles with a z average particle size in the range of 2 μm to 20 μm as measured by DLS can be prepared substantially as described above, but without end-capping ligands.
[0018] Compositions comprising latex and cerium (III) carbonate particles are useful in the field of coating compositions, especially coating compositions comprising pigments or colorants or both. Pigments include opaque pigments and extenders. Opaque pigments include TiO 2 ,BaSO 4 and organic hollow sphere polymer particles (HSP). TiO 2 Can be anatase or rutile, and passivated or unpassivated. TiO 2 A commercial example is Ti-Pure-R706 TiO 2 and DeGussa P25 TiO 2 Photocatalysts. Compositions may include anatase and rutile, passivated and unpassivated TiO 2 combination.
[0019] Suitable extenders include carbonates, silica, silicates, aluminosilicates, phosphates, and non-hollow organic microspheres. More specific examples of extenders include talc, clay, mica, sericite, CaCO 3 , nepheline, feldspar, wollastonite, kaolinite, dicalcium phosphate and diatomaceous earth.
[0020] The colorant may be organic or inorganic, dispersible (colorant) or soluble (dye). Examples of suitable colorants include methylene blue, phthalocyanine blue, phthalocyanine green, monoaryl yellow, diaryl yellow, benzimidazolone yellow, heterocyclic yellow, DNA orange, pyrrole orange, quinacridone magenta, quinacridone violet, dioxazine violet, quinacridone red, naphthol red, pyrrole red, metallized azo red, non-metallized azo red, carbon black, lamp black, black iron oxide, yellow iron oxide, brown iron oxide, and red iron oxide.
[0021] In another aspect, the invention is a composition comprising a polymer such as poly(methyl methacrylate) (PMMA) dissolved in a solvent such as chloroform in the presence of dispersed cerium (III) carbonate particles. The composition of this aspect of the invention is useful, for example, in the housing of an automotive headlamp.
[0022] In another aspect, the present invention is a composition comprising cerium (III) carbonate particles and a neat polymer. This composition can be prepared by mixing cerium (III) carbonate particles with an extruded polymer melt.
[0023] Examples of suitable polymers include polyacrylates, poly(styrene-acrylates), polystyrene, polyvinyl acetate, polyurethanes, poly(vinyl acetate-acrylates), silicones, epoxies, polyolefins, celluloses, and polysilicates.
[0024] Cerium (III) carbonate nanodispersions are particularly useful in applications such as latex paint formulations where color and gloss retention are desirable.
[0025] Example 1-4 - Preparation of aqueous nanodispersion of cerium (III) carbonate particles
[0026] In the following examples, the z-average particle size was determined by dynamic light scattering.
[0027] Example 1 - Preparation of an aqueous dispersion of EDTA-stabilized nanosized cerium (III) carbonate particles
[0028] An aqueous solution of cerium (III) ammonium nitrate tetrahydrate (2 g in 100 mL DI water) was added to a 250 mL plastic vial. EDTA (50 mg) and ammonium carbonate (1 g) were dissolved in water (50 mL) and then added to the solution of cerium (III) ammonium nitrate tetrahydrate within 25 s while stirring (600 rpm) for 10 min. The pH of the mixture was observed to be 8.0 ± 0.3.
[0029] The product mixture was divided into four 40 mL centrifuge tubes and then centrifuged at 20,000 rpm for 6 min. The white product in each tube was collected and washed with 25 mL of water (including 5 min vortex mixing) to ensure removal of soluble nitrates and excess ammonium carbonate. The final product after washing and centrifugation was obtained as a wet paste with a solid content of 20 wt%.
[0030] To study the effect of EDTA loading on the properties of cerium (III) carbonate, this example was repeated twice using 100 mg and 500 mg of EDTA. The z-average particle size of the cerium carbonate particles was found to be 125 nm (50 mg EDTA), 118 nm (100 mg EDTA) and 114 nm (500 mg EDTA).
[0031] Example 2 - Preparation of an aqueous dispersion of NTA-stabilized nanosized cerium (III) carbonate particles
[0032] The procedure described in Example 1 was essentially followed, except that NTA (65 mg) was used instead of EDTA as the capping ligand. The final product after washing and centrifugation was obtained as a wet paste with a solid content of 20 wt%.
[0033] This example was repeated using 32.5 mg of NTA. The z-average particle sizes of the cerium carbonate particles were found to be 157 nm (32.5 mg NTA) and 115 nm (65 mg NTA).
[0034] Example 3 - Preparation of an aqueous dispersion of PIDA-stabilized nanosized cerium (III) carbonate particles
[0035] An aqueous solution of cerium (III) ammonium nitrate tetrahydrate (2 g in 100 mL DI water) was added to a 250 mL plastic bottle. PIDA (72 mg) and ammonium carbonate (1 g) were dissolved in water (50 mL) and then added to the solution of cerium (III) ammonium nitrate tetrahydrate within 25 s while stirring (600 rpm) for 10 min. The pH of the mixture was observed to be 8.0 ± 0.3.
[0036] The product mixture is divided into four 40mL centrifuge tubes and then centrifuged for 6min at 20,000rpm. The white product in each tube is collected and washed with 25mL water (including 5min vortex mixing) to ensure that soluble nitrates and excess ammonium carbonate are removed. The final product after washing and centrifugation is obtained as a wet paste with 20wt% solid content. It is found that the z average particle size of cerium carbonate particles is 105nm.
[0037] Example 4 - Preparation of an aqueous dispersion of PAA-stabilized nanosized cerium (III) carbonate particles
[0038] An aqueous solution of cerium (III) ammonium nitrate tetrahydrate (2 g in 100 mL DI water) was added to a 250 mL plastic bottle. PAA (500 mg of a 50% aqueous solution, MW = 2000 g / mol) and ammonium carbonate (1 g) were dissolved in water (50 mL) and then added to the solution of cerium (III) ammonium nitrate tetrahydrate within 25 s with stirring (600 rpm) for 10 min. The pH of the mixture was observed to be 8.0 ± 0.3.
[0039] The product mixture was divided into four 40 mL centrifuge tubes and then centrifuged at 20,000 rpm for 6 min. The white product in each tube was collected and washed with 25 mL of water (including 5 min vortex mixing) to ensure removal of soluble nitrates and excess ammonium carbonate. The final product after washing and centrifugation was obtained as a wet paste with a solid content of 20 wt%.
[0040] The example was repeated twice using 1.1 g and 2.2 g of 50% aqueous PAA.The z-average particle size of the cerium carbonate particles determined by dynamic light scattering (DLS) was found to be 105 nm (0.5 g PAA), 105 nm (1.1 g PAA) and 20 nm (2.2 g NTA).
[0041] Example 5-7 - Preparation of coating formulations using dyes and colorants
[0042] In the following preparation, the acrylic adhesive had the following characteristics: (49BA / 50MMA / 1MAA), z-average particle size = 98nm, solids content 40.2 wt.%.
[0043] Preparation of paint formulations using dyes:
[0044] Two separate dispersions were prepared as follows:
[0045] A. Ti-Pure-R706 TiO 2 (3.5 g), optional Ti-Pure-R706 TiO 2 10% by weight DeGussa P25 TiO 2 Photocatalyst, TAMOL TM 1124 dispersant (trademark of Dow Chemical Company or its affiliates, 0.3 wt. % relative to the weight of the pigment), 1 M NH 4 OH (10 μL) and 3.5x10 -4 An aqueous solution of Congo red dye or methylene blue dye (0.7 mL) was stirred at 1700 rpm in a ZrO 2 beads (10 mm) to form TiO 2Slurry. Removal of ZrO from slurry 2 The beads were added and then additional amounts of dye solution (1.27 mL) were added to the slurry over time. The mixture was then mixed (3500 rpm for 3 min) to obtain 4.65 g of a 75 wt.% pigment slurry.
[0046] B. Combine 2 wt.% to 5 wt.% cerium (III) carbonate solids (relative to the weight of Ti-Pure-R706 in step A) (20% solids wet paste prepared as described above without or with a capping ligand, as described in Example 2) with water (0.86 mL to 0.44 mL, depending on the solids). 4 The pH of the resulting solution was adjusted to pH 9 by using 2% HCl. The mixture was sheared (3500 rpm for 4 min) and then sonicated (10 min).
[0047] The slurry from step A was mixed with acrylic binder (12.79 g) under stirring. The dispersion from step B was mixed with the slurry from step A and the mixture was sheared (3500 rpm for 1 min). ACRYSOL TM 2020E thickener (trademark of The Dow Chemical Company or its affiliates, 0.6 g) was added to the mixture and mixed (3500 rpm for 3 min) to obtain a final paint formulation at about 16% pigment volume concentration (PVC).
[0048] Prepare paint formulations with colorants:
[0049] Ti-Pure-R706 TiO 2 (4.6g),TAMOL TM 1124 dispersant (0.3 wt. % relative to pigment weight), 1M NH 4 OH (10 μL), DeGussa P25 TiO 2 Photocatalyst (0.36 g), Colortrend Organic Red 808 colorant (0.44 g) and water (1.53 g) were stirred at 2100 rpm in a ZrO 2 Removal of ZrO from the slurry 2 The slurry was mixed again (3500 rpm, 3 min) to obtain 7 g of 75 wt.% pigment slurry. The slurry was mixed with the dispersion described in Step B (except only the cerium (III) carbonate was prepared according to Example 2) to form a final paint formulation with a PVC of about 16%.
[0050] UV-induced photodegradation of coatings
[0051] The paint formulation was applied on a polyacrylic acid substrate using a 3 mil bar applicator. The applied coating was dried for 72 h under ambient conditions. The dried coating was then irradiated under 254 nm UV light (140-150 Lux) for 4 h.
[0052] A portion of the coating (200 mg) was scraped off the polyacrylic acid substrate, combined with 1 mL of ethanol, and sonicated for 15 min. The mixture was then vortexed for 5 min, and the supernatant containing the residual dye was analyzed by UV-vis spectroscopy to determine the extent of dye degradation.
[0053] Example 5 - Dye degradation by UV-Vis, containing P25
[0054] As described above, when containing Ti-R706-TiO 2 When a sample of , DeGussa P25, acrylic adhesive, Congo red dye, and cerium (III) carbonate without a capping ligand was exposed to UV light, the dye degraded to 8%, compared to 40% without cerium (III) carbonate.
[0055] Example 6 - Dye degradation by UV-Vis without P25
[0056] As described above, when containing Ti-R706-TiO 2 When a sample of 1,000 Å, acrylic adhesive, methylene blue dye, and cerium (III) carbonate without a capping ligand was exposed to UV light, the dye was degraded to 0%, compared to 15% without cerium (III) carbonate.
[0057] Example 7 - Color degradation by UV-vis, containing P25
[0058] As described above, when the Ti-R706-TiO 2 When a sample of cerium(III) carbonate with a capping ligand as described in Example 2 was exposed to UV light, the color retention was found to be completely maintained. In contrast, the sample without cerium(III) carbonate showed significant color loss.
[0059] UV-induced photodegradation of polymethyl methacrylate:
[0060] Dissolve a) in CHCl 3A mixture of a) PMMA and b) cerium (III) carbonate particles (prepared as in Example 1 or 3; 2 or 5 wt.% based on PMMA) was poured into a watch glass and allowed to dry for 16 h under ambient conditions. After drying for 16 h, the PMMA film was then irradiated under 254 nm UV light (140-150 Lux) for 4 h.
[0061] Example 8 - UV Photodegradation of PMMA with EDTA-capped Cerium(III) Carbonate
[0062] No yellowing was observed for the irradiated PMMA film containing cerium (III) carbonate capped with EDTA (2 wt % based on the weight of PMMA). In contrast, the cast film without cerium (III) carbonate exhibited significant yellowing.
[0063] Example 9 - UV Photodegradation of PMMA with PIDA-terminated Cerium(III) Carbonate
[0064] No yellowing was observed for the irradiated PMMA film containing cerium (III) carbonate end-capped with PIDA (5 wt % based on the weight of PMMA). In contrast, the cast film without cerium (III) carbonate exhibited significant yellowing.
[0065] Studies have shown that cerium (III) carbonate improves discoloration and significantly reduces undesirable color formation in coatings prepared from the coating formulations.
Claims
1. Use of a composition for maintaining color and gloss in an exterior coating by stabilizing particles against agglomeration with a capping ligand, wherein the composition comprises an aqueous dispersion of cerium (III) carbonate particles having a z-average particle size in the range of 5 nm to 500 nm, the composition further comprising a capping ligand, the capping ligand being an amine carboxylic acid or salt thereof, an amine phosphonic acid or salt thereof, or a polymer functionalized with a carboxylic acid group or salt thereof, the concentration of the cerium (III) carbonate in water being in the range of 0.2 wt % to 25 wt % based on the weight of water and cerium (III) carbonate.
2. The use according to claim 1, wherein The cerium (III) carbonate particles have a z-average particle size in the range of 50 nm to 200 nm; wherein the end-capping ligand is aminoacetic acid or a salt thereof, an amine phosphonic acid or a salt thereof, or a polymer functionalized with a carboxylic acid group or a salt thereof.
3. The use according to claim 2, wherein The end-capping ligand is ethylenediaminetetraacetic acid, ethylenediaminediacetic acid, nitrilotriacetic acid, polyacrylic acid or N-(phosphonomethyl)iminodiacetic acid.
Citation Information
Patent Citations
Preparation method of cerium carbonate and cerium oxide
CN102161497A
Coloring material dispersion liquid for color filter, color resin composition for color filter, color material, color filter, liquid crystal display apparatus, and light emitting display apparatus
CN107111023A
Novel water-based drier and preparation method thereof
CN109321027A
Ultraviolet-shielding agent, method for the preparation thereof and cosmetic composition compounded therewith
US5478550A